Implementation of TSI requirements in railway infrastructure modernization projects of Ukraine in the context of EU transport system integration - Olena Bal; Volodymyr Tverdomed; Oresta Kovalchuk; Liliia Solodiak; Nataliia Borys (Збірник наукових праць Державного університету інфраструктури та технологій: серія "Транспортні системи і технології")
The article is devoted to the analysis of technical and institutional aspects of the implementation of the requirements of the Technical Specifications for Interchangeability (TSI) in projects for the modernization of the railway infrastructure of Ukraine with financial support from the European Union within the framework of the Connecting Europe Facility (CEF) program. The current regulatory and institutional framework is analyzed, barriers and risks are identified, and models of cooperation with European certification bodies are proposed. The main attention is paid to the project "Modernization of the Mostyska-Lviv railway connection" as a representative example of integration into the TEN-T network. The article substantiates the feasibility of implementing a pilot model of cooperation between Ukrainian institutions and European certification bodies to confirm the compliance of design solutions with the TSI requirements. Special attention is paid to the issues of ensuring traffic safety, risk management, environmental safety, and compliance with functional safety standards, which are critically important for the certification of infrastructure facilities and obtaining funding from the EU. The pilot model of cooperation between Ukrainian participants and European certification bodies proposed in the article can become a scalable tool for ensuring TSI compliance. Institutional support from ERA and CINEA, technical dialogue, national capacity building and a multidisciplinary approach to project evaluation are the determining conditions for Ukraine's full participation in the European railway system.